Factors Influencing the Occurrence of Ispa Disease in Excavation C Workers in the Work Area of the Gonengganti Health Center - Fitriana Fitriana; Budiman Budiman; Hamidah Hamidah (Indonesian Health Journal, 2026)
This study aims to analyze the factors that affect the incidence of ISPA (Infeksi Saluran Pernafasan Atas) in excavation C workers in the working area of the Gonengganti Health Center, Donggala Regency. This study is a quantitative research with a cross-sectional design. The research population is all excavation C workers in the working area of the Gonengganti Health Center, with a total sample of 83 people taken using the total sampling technique. Data were collected through a structured questionnaire that included dust exposure levels, PPE use, duration of dust exposure, and smoking history. Data analysis was carried out univariately, bivariately using chi-square test, and multivariately using logistic regression. The results of the bivariate analysis showed that dust exposure level, PPE use, dust exposure duration, and smoking history had a significant relationship with the incidence of ISPA in excavation C workers (p < 0.05). Multivariate analysis showed that dust exposure level and PPE use were the most dominant factors associated with ISPA incidence, with odds ratio (OR) values > 1, indicating that workers with high dust exposure and not using PPE consistently have a greater risk of experiencing ISPA than other workers. The conclusion of this study shows that the incidence of ISPA in C excavation workers is influenced by work environment factors and worker behavior. Therefore, efforts are needed to control dust exposure, increase compliance with PPE use, regulate work duration, and provide education on the dangers of smoking as preventive measures to reduce the risk of ISPA in excavation C workers.